Modeling and Stability of Prey - Predator System Involving Infectious Disease in Each Population with Harvesting of the Prey - Ali, Nidhal Faisal (Al-Nahrain Journal of Science, 2018)
In this paper, a mathematical model consisting of the prey- predator model involving disease in both the population with harvesting of prey is proposed and analyzed. The existence, uniqueness and boundedness of the solution are discussed. The existences and the stability analysis of all possible equilibrium points are studied. Finally the effects both of the disease and harvest on the dynamical behavior the model are discussed numerically.